Method for preparing solidified self-forming slow-release heparin antibacterial matrix ZIF material
By using polyvinyl alcohol as a polymerization linker, the process is simplified and the encapsulation rate is improved, and the cured self-forming sustained release heparin antibacterial matrix ZIF material is prepared, which solves the problems of high cost and fast drug release in the prior art. The sustained release and antibacterial effects on artificial blood vessels are achieved.
Patent Information
- Application Number
- CN202411329899.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2024-12-27
AI Technical Summary
The synthesis process of existing ZIF materials requires strict Zn2+ concentration of raw materials, high cost of solution system, and complex nano-scale grain forming process, resulting in high prices of terminal products, limiting its large-scale industrial and medical applications. In addition, existing sustained-release heparin materials are easily contaminated by pathogenic bacteria in medical use, and the drug release speed is too fast, making it difficult to achieve sustained-release effect.
Using polyvinyl alcohol as a polymerization linker, the solidified self-forming sustained-release heparin antibacterial matrix ZIF material is prepared by primary growth method and freeze-drying method, simplifying the process, improving the encapsulation and release rate of heparin sodium, and ensuring that the drug release kinetics are in line with need. The specific steps include dissolving Zn(NO3)2·6H2O and 2-methylimidazole, adding sodium heparin, leaving it stand after ultrasound, centrifuge and drying, then freezing in liquid nitrogen and curing under dynamic vacuum to form HP@ZIF- 8 Materials.
It realizes the preparation of ZIF materials with convenient operation and low cost, improves the encapsulation and release rate of sodium heparin, ensures the sustained release effect and antibacterial properties of the drug. It is suitable for artificial blood vessel surfaces, and can achieve anticoagulation and inhibition at the same time. bacteria function.
Smart Images

Figure CN119185656A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of ZIF material preparation, and in particular relates to a method for preparing a solidified self-forming sustained-release heparin antibacterial matrix ZIF material. Background Art
[0002] ZIFs, zeolite imidazolate framework materials, are made by using metal ions Zn 2+ and Co 2+ Porous crystalline polymers with zeolite-like structures composed of imidazole or imidazole derivatives. Due to its polymerization characteristics, it has the properties of porous materials and has many excellent physical and chemical properties such as adjustable micropore size and shape. And because its metal ion part has natural antibacterial properties, its functionality has been further expanded to the scope of screening and inhibiting bacteria. However, for a long time, due to the synthetic process of raw material Zn 2+ The stringent requirements on concentration, the high price cost of the solution system itself, and the complex and difficult process of nano-scale grain forming have resulted in high terminal prices of ZIF products, limiting their large-scale industrial and medical applications.
[0003] Sustained-release heparin sodium is usually used as a model research system to examine and study the performance of sustained-release heparin. Heparin is a bioactive reagent with anticoagulant properties. Medical scenarios such as artificial blood vessels require a significant sustained-release effect of heparin to balance the non-traumatic coagulation of blood.
[0004] At the same time, in medical applications, sustained-release heparin materials have the risk of being out of the sterile environment for a long time and being contaminated by pathogenic bacteria. Therefore, its inhibitory effect on Gram-negative and Gram-positive bacteria is also one of the research directions with obvious research value.
[0005] Zheng J. Fabrication of pH-sensitive magnetic metal-organic framework for controlled-release of heparin[J]. 2022 Using ZIF-8 to design a pH-responsive carrier, a method for encapsulation and release of polysaccharides such as heparin (HP), fucoidan sulfate (FuS), fucosylated chondroitin sulfate (FCS) and hyaluronic acid (HA) was disclosed. Fe 3 O 4 / HP@ZIF-8, composite Fe 3 O 4 / HP@ZIF-8 has good dispersibility in water and can be easily guided to a specific location under the action of an external magnetic field. The introduction of magnetic substances may promote the drug to reach the lesion site through the external magnetic field, but this method is difficult to operate. There are too many uncertain factors caused by magnetic field control, and it is difficult to achieve the expected effect. At pH = 5.6, HP@ZIF-8 and Fe 3 O 4 / HP@ZIF-8 composites released 27.7% and 46% of the total mass within 30 min, respectively. At pH = 7.4, the release efficiency of HP@ZIF-8 and Fe 3 O 4 The release efficiency of the / HP@ZIF-8 composite material within 30 minutes was 17.2% and 28.2%, respectively. Therefore, the pH needs to be strictly controlled when using this method for application, and the drug release effect of this method is too fast to achieve the purpose of sustained release and cannot better meet the drug release kinetics. Summary of the invention
[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a solidified self-forming sustained-release heparin antibacterial matrix ZIF material, and prepare an artificial blood vessel original matrix using polyvinyl alcohol (PVA) as a polymer linker. The original growth method and freeze-drying method are mainly adopted, the process is simple and the cost is low, the encapsulation rate of heparin sodium is improved, and the release rate of heparin sodium is more in line with the drug release kinetics.
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a solidified self-forming sustained-release heparin antibacterial matrix ZIF material, comprising the following steps:
[0009] Step 1: Zn(NO 3 ) 2 6H 2 O is dissolved in a mixed solution of alcohol and water, and solution A is obtained by ultrasonication;
[0010] Step 2: dissolving 2-methylimidazole and heparin sodium in an alcohol-water mixed solution, and ultrasonicating to obtain solution B;
[0011] Step 3: Add solution B dropwise into solution A, and mix at room temperature to obtain a mixed solution, then stand at room temperature, centrifuge, wash, and dry to obtain HP@ZIF-8;
[0012] Step 4: Dissolve the hydrophilic organic polymer in deionized water, add HP@ZIF-8, stir for 2-4 hours, freeze the suspension in liquid nitrogen at -190 to -200°C for 4-6 minutes, and finally place it under dynamic vacuum for 20-25 hours to obtain a solidified self-forming sustained-release heparin antibacterial matrix ZIF material.
[0013] Furthermore, the hydrophilic organic polymer is polyvinyl alcohol, polyethylene glycol or polyvinyl pyrrolidone.
[0014] Furthermore, the mass ratio of the hydrophilic organic polymer to HP@ZIF-8 is 1:9-1:18.
[0015] Furthermore, Zn(NO 3 ) 2 6H 2 The molar ratio of O to 2-methylimidazole is 1:2-1:8.
[0016] Furthermore, the mass ratio of 2-methylimidazole to heparin sodium is 1:0.002-1:0.02.
[0017] Further, in step 1, the Zn 2+ The concentration is 50-1000ppm. Preferably, the Zn 2+ The concentration is 500-1000ppm.
[0018] The solidified self-forming sustained-release heparin antibacterial matrix ZIF material prepared by the above method is used in artificial blood vessels.
[0019] Advantages and beneficial effects of the present invention:
[0020] (1) The present invention proposes for the first time to use ZIF-8 to encapsulate sodium heparin as the angiogenic matrix, and simultaneously studies its sustained-release effect and antibacterial effect, so that the composite material as a vascular surface coating can not only achieve anticoagulant function but also achieve the function of inhibiting bacteria and preventing bacterial infection.
[0021] (2) The present invention uses polyvinyl alcohol as the original matrix polymer of artificial blood vessels, which improves the hydrophilicity and mechanical properties of the material and does not have a negative impact on the sustained-release antibacterial effect. It is easy to operate and can better control the expected results. A composite material that can both sustain the release of heparin sodium and achieve an antibacterial effect is invented.
[0022] (3) The present invention introduces a hydrophilic polymer into HP@ZIF-8 by a low-temperature curing method, which can not only improve the hydrophilicity of the material, making it have better biocompatibility and anti-protein adhesion ability, but also reduce the dispersibility of the material, making it easier to collect, and at the same time improve the mechanical properties of the material. The freeze-drying method has a simple process and is easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Flow chart of HP@ZIF-8 prepared in Example 1;
[0024] Figure 2This is a flow chart of the solidified self-forming sustained-release heparin antibacterial matrix ZIF material prepared in Example 1;
[0025] Figure 3 This is the electron microscopy image of PVA-cured HP@ZIF-8. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0027] Example 1
[0028] Take 0.0019g Zn(NO 3 ) 2 6H 2 O and 0.0011g 2-methylimidazole were dissolved in 100ml of alcohol-water solution, respectively, recorded as solution A and solution B, and 0.1g of 2-methylimidazole was added to solution B to a concentration of 0.72mg·mL -1 Heparin sodium, Zn(NO 3 ) 2 6H 2 The molar ratio of O to 2-methylimidazole is 1:2, and the two solutions are ultrasonically treated for later use. Solution B is added dropwise to solution A, and the resulting mixture is stirred at room temperature for 1 hour. After standing for 24 hours, the solid is collected by centrifugation and washing, and washed 3 times with deionized water and anhydrous ethanol respectively. The solid is air-dried at room temperature to obtain HP@ZIF-8. 10 mg of polyvinyl alcohol (PVA) is dissolved in 1 mL of deionized water, 90 mg of HP@ZIF-8 is added, and after stirring for 3 hours, the suspension is placed in a beaker and frozen in liquid nitrogen at -196°C for about 5 minutes. Finally, the beaker is placed under dynamic vacuum for 24 hours to obtain a solidified self-forming sustained-release heparin antibacterial matrix ZIF material. The maximum absorption wavelength and standard working curve of the HP@ZIF-8 solution are measured using an ultraviolet spectrophotometer, and the encapsulation efficiency of the ZIF material for sodium heparin is 83%.
[0029] Example 2
[0030] Take 0.0038g Zn(NO 3 ) 2 6H 2 O and 0.0042 g 2-methylimidazole were dissolved in 100 ml of alcohol-water solution, respectively, recorded as solution A and solution B, and 0.1 g of 2-methylimidazole was added to solution B to a concentration of 0.72 mg mL -1 Heparin sodium, Zn(NO 3 ) 2 6H 2The molar ratio of O to 2-methylimidazole is 1:4, and the two solutions are ultrasonically treated for later use. Solution B is added dropwise to solution A, and the resulting mixture is stirred at room temperature for 1 hour. After standing for 24 hours, the solid is collected by centrifugation and washing, and washed 3 times with deionized water and anhydrous ethanol respectively. The solid is air-dried at room temperature to obtain HP@ZIF-8. 10 mg of polyvinyl alcohol (PVA) is dissolved in 1 mL of deionized water, 90 mg of HP@ZIF-8 is added, and after stirring for 3 hours, the suspension is placed in a beaker and frozen in liquid nitrogen at -196°C for about 5 minutes. Finally, the beaker is placed under dynamic vacuum for 24 hours to obtain a solidified self-forming sustained-release heparin antibacterial matrix ZIF material. The maximum absorption wavelength and standard working curve of the HP@ZIF-8 solution are measured using an ultraviolet spectrophotometer, and the encapsulation efficiency of the ZIF material for sodium heparin is 94%.
[0031] Example 3
[0032] Take 0.0057g Zn(NO 3 ) 2 6H 2 O and 0.0095 g 2-methylimidazole were dissolved in 100 ml of alcohol-water solution, respectively, recorded as solution A and solution B, and 0.1 g of 0.72 mg mL -1 Heparin sodium, Zn(NO 3 ) 2 6H 2 The molar ratio of O to 2-methylimidazole is 1:6, and the two solutions are ultrasonically treated for later use. Solution B is added dropwise to solution A, and the resulting mixture is stirred at room temperature for 1 hour. After standing for 24 hours, the solid is collected by centrifugation and washing, and washed 3 times with deionized water and anhydrous ethanol respectively. The solid is air-dried at room temperature to obtain HP@ZIF-8. 10 mg of polyvinyl alcohol (PVA) is dissolved in 1 mL of deionized water, 90 mg of HP@ZIF-8 is added, and after stirring for 3 hours, the suspension is placed in a beaker and frozen in liquid nitrogen at -196°C for about 5 minutes. Finally, the beaker is placed under dynamic vacuum for 24 hours to obtain a solidified self-forming sustained-release heparin antibacterial matrix ZIF material. The maximum absorption wavelength and standard working curve of the HP@ZIF-8 solution are measured using an ultraviolet spectrophotometer, and the encapsulation efficiency of the ZIF material for sodium heparin is 92%.
[0033] Example 4
[0034] Take 0.0076g Zn(NO 3 ) 2 6H 2 O and 0.0168 g 2-methylimidazole were dissolved in 100 ml of alcohol-water solution, respectively, recorded as solution A and solution B, and 0.1 g of 2-methylimidazole was added to solution B to a concentration of 0.72 mg mL -1 Heparin sodium, Zn(NO 3) 2 6H 2 The molar ratio of O to 2-methylimidazole is 1:8, and the two solutions are ultrasonically treated for later use. Solution B is added dropwise to solution A, and the resulting mixture is stirred at room temperature for 1 hour. After standing for 24 hours, the solid is collected by centrifugation and washing, and washed 3 times with deionized water and anhydrous ethanol respectively. The solid is air-dried at room temperature to obtain HP@ZIF-8. 10 mg of polyvinyl alcohol (PVA) is dissolved in 1 mL of deionized water, 90 mg of HP@ZIF-8 is added, and after stirring for 3 hours, the suspension is placed in a beaker and frozen in liquid nitrogen at -196°C for about 5 minutes. Finally, the beaker is placed under dynamic vacuum for 24 hours to obtain a solidified self-forming sustained-release heparin antibacterial matrix ZIF material. The maximum absorption wavelength and standard working curve of the HP@ZIF-8 solution are measured using an ultraviolet spectrophotometer, and the encapsulation efficiency of the ZIF material for sodium heparin is 83%.
[0035] As the amount of 2-methylimidazole relative to Zn increased, the growth rate of ZIF-8 accelerated, and the drug loading and encapsulation efficiency increased. 3 ) 2 6H 2 When the molar ratio of O to 2-methylimidazole is 1:4, the encapsulation efficiency is the highest, while continuing to increase dimethylimidazole has no obvious effect on improving the encapsulation efficiency.
[0036] Comparative Example 1
[0037] The difference from Example 2 is that the concentration of heparin sodium is 0.18 mg·mL -1 , the encapsulation efficiency was 92%.
[0038] The drug showed a similar burst release phase within 1-6 hours, with a cumulative release of 501 μg. Within 6-9 hours, the release rate gradually slowed down, reaching a sustained release plateau around 15 hours, and the cumulative release within 24 hours was 606.81 μg, 0.72 mg·mL -1 The sample synthesized with heparin sodium concentration had the best antibacterial effect on Escherichia coli, with an inhibition rate of 82.57%. HP concentration was 0.18 mg·mL -1 When the drug was added, the release rate was the fastest within 3 hours, with a cumulative release of 129.45 μg. As time went on, the release rate gradually slowed down, reaching a sustained release equilibrium within 6 hours, and the cumulative release within 24 hours was 160.24 μg.
[0039] Comparative Example 2
[0040] The difference from Example 2 is that the concentration of heparin sodium is 0.36 mg·mL -1 , the encapsulation efficiency was 93%.
[0041] By comparing with Example 2, it was found that when the HP concentration was 0.36 mg·mL-1 When the drug was taken, it showed a similar burst release phase within 1-6 hours, with a cumulative release of 431 μg. Within 6-9 hours, the release rate gradually slowed down, reaching a sustained release equilibrium around 15 hours. The cumulative release within 24 hours was 535.33 μg.
[0042] Comparative Example 3
[0043] The difference from Example 2 is that the concentration of heparin sodium is 1.44 mg·mL -1 , the encapsulation efficiency is 90%.
[0044] By comparing with Example 2, it was found that when the HP concentration was 1.44 mg·mL -1 HP reached equilibrium within 9 hours. Among them, 1-6 hours was the burst release stage, with a cumulative release of 305.1 μg. Subsequently, the release rate slowed down, reaching a release equilibrium in about 12 hours, and the cumulative release in 24 hours was 359.15 μg.
[0045] When the HP concentration is 0.36 mg mL -1 and 0.72 mg mL -1 When the HP concentration is 0.18 mg·mL -1 and 1.44 mg mL -1 This indicates that within a certain range, increasing the HP concentration can prolong the sustained-release time of the drug and increase the cumulative release amount.
[0046] Comparative Example 4
[0047] The difference from Example 2 is that no polymer is used for low temperature curing.
[0048] Take 0.0038g Zn(NO 3 ) 2 6H 2 O and 0.0042 g 2-methylimidazole were dissolved in 100 ml of alcohol-water solution, respectively, recorded as solution A and solution B, and 0.1 g of 2-methylimidazole was added to solution B to a concentration of 0.72 mg mL -1 Heparin sodium, Zn(NO 3 ) 2 6H 2 The molar ratio of O to 2-methylimidazole was 1:4, and the two solutions were ultrasonicated for later use. Solution B was added dropwise to solution A, and the resulting mixture was stirred at room temperature for 1 hour. After standing for 24 hours, the solid was collected by centrifugation and washed, and washed with deionized water and anhydrous ethanol for 3 times each. The solid was air-dried at room temperature to obtain HP@ZIF-8.
[0049] By comparison with Example 2, 2Adsorption-desorption characterization found that the pore size after the introduction of polymer is about 1.5 to 1.84 times that of the sample without the introduction of polymer. Due to the coating of HP@ZIF-8 by the polymer, heparin sodium will go through more paths than HP@ZIF-8 during the sustained release to the outside of the sample, resulting in a part of the residue in the path, and the cumulative amount of sustained release in 24 hours will be relatively reduced. It is precisely because the heparin sodium remaining on the surface of the polymer may be released over a longer period of time.
[0050] Comparative Example 5
[0051] The difference from Example 2 is that 5 mg of PVA was used for the experiment.
[0052] When the PVA dosage was 5 mg, the release behavior of the sample changed significantly. Within 1 hour, the sample released 150.62 μg of sodium heparin, which was about twice that of other samples. This shows that at a low PVA concentration ratio, the drug release rate of the material is too fast, which is not conducive to achieving slow release and continuous drug administration.
[0053] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. A method for preparing a solidified self-forming sustained-release heparin antibacterial matrix ZIF material, characterized in that: The following steps are involved: Step 1: dissolve Zn(NO3)2·6H2O in a mixed solution of alcohol and water, and obtain solution A by ultrasonication; Step 2: dissolving 2-methylimidazole and heparin sodium in an alcohol-water mixed solution, and ultrasonicating to obtain solution B; Step 3: Add solution B dropwise into solution A, stir at room temperature, and obtain a mixed solution after mixing. Then, after standing at room temperature, centrifuge, wash, and dry to obtain HP@ZIF-8; Step 4: Dissolve the hydrophilic organic polymer in deionized water, add HP@ZIF-8, stir for 2-4 hours, freeze the suspension in liquid nitrogen at -190 to -200°C for 4-6 minutes, and finally place it under dynamic vacuum for 20-25 hours to obtain a solidified self-forming sustained-release heparin antibacterial matrix ZIF material.
2. The method according to claim 1, characterized in that The hydrophilic organic polymer is polyvinyl alcohol, polyethylene glycol or polyvinyl pyrrolidone.
3. The method according to claim 1, characterized in that The mass ratio of the hydrophilic organic polymer to HP@ZIF-8 is 1:9-1:
18.
4. The method according to claim 1, characterized in that: The molar ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:2-1:
8.
5. The method according to claim 1, characterized in that The mass ratio of 2-methylimidazole to heparin sodium is 1:0.002-1:0.
02.
6. The method according to claim 1, characterized in that: In step 1, the Zn 2+ The concentration is 50-1000ppm.
7. The method according to claim 5, characterized in that: The Zn 2+ The concentration is 500-1000ppm.